Comparison between Low Flow and High Flow Sevoflurane Isocapnic Technique to Achieve Early Recovery after Surgery (ERAS) - Adinda Putra Pradhana (Journal of Global Pharma Technology, 2019)
Objective. The purpose of this study was to compare recovery time between low flow and high flow sevoflurane isocapnic anesthesia techniques, as well as the total consumption of sevoflurane.Design. This study was an observational single-blind randomized trialSetting. Operating room.Patients. Total 40 patients from both gender, 18 to 60 years old, BMI 18.5-29.99 kg/m2 with physical status ASA I or II, that scheduled for elective surgery under general anesthesia approximately between 3-5 hours were selected for this study.Intervention. Selected patients divided randomly into two groups (n=20 each). First group was given low flow sevoflurane, delivered with initial flow 6 L/min until MAC 0.9 or expiration level of sevoflurane 2.2 vol% then reduced flow to 0.5 L/min; second group with high flow technique 4L/min after induction.Measurement. The duration of operation, duration of anesthesia, time reaching of BIS 75, eye-opening with command, extubation, moving into the recovery room and when reaching Modified Aldrete score 10.Main Results: Based on statistics, sample characteristics, hemodynamic conditions, length of anesthesia and number of fentanyl were not significantly different. There was a significant difference on post anesthesia recovery time between low flow and high flow anesthesia time BIS 75: 1.7 (± 0.801) vs 7.05 (± 3.956), p<0.001, eye-opening time: 5.45 (± 3.82) vs. 14.86 (± 7.945 ), p<0.001, extubation time: 5.8 (± 2.783) vs. 15.29 (± 8.776), p<0.001, moving into recovery room: 15.35 (± 5.133) vs. 23.52 (± 12.213), p=0.021, time reaching modified aldrete 10: 8.95 (± 4.211) vs. 29 (± 18,091), p<0.001).Conclusion: Recovery time after general anesthesia using low flow sevoflurane isocapnic anesthesia technique is faster than the high flow anesthesia technique with less sevoflurane consumption.